Antagonist activity of Trichoderma spp. against Sarocladium oryzae on sheath rot disease of rice cultivation in vivo assays / Ariff Abdul Somad Hamzah - Hamzah, Ariff Abdul Somad (Faculty of Plantation and Agrotechnology, 2019)
Sheath rot (Sarocladium oryzae) disease was one of a serious disease that affects the rice production in Malaysia. The sheath rot has widely infest in many rice cultivation areas in Malaysia and has been reported to result at about 40% to 60% loss of revenue. Due to the wide spread of diseases infestation, farmers tend to increase the usage of pesticide to overcome the diseases that might harm the environment and increase the cost of maintenance. Therefore, this study was conducted to measure the performance of Trichoderma sp. suspension by pathogenicity test against Sarocladium oryzae. This study is conducted under greenhouse condition to specify the ability of soil borne pathogen specimens which is Trichoderma sp. to counter, resist, or withstand against the causal agent of sheath rot disease which is Sarocladium oryzae in MR219 rice variety. This biological control research is tested by antagonistic activity (in-vitro) by conversion of both pathogen into conidial suspension and applied or tested on the rice crop. Both severity and results were recorded and it was found that Trichoderma sp. showed the ability to inhibit or stop the severity or Sarocladium oryzae pathogen infection on the rice crop. As for conclusion that can be drawn from this study are the method can be further develop into an alternative method in controlling sheath rot or maybe other diseases on rice crop in the future as biological control have become a trend and step among agriculture agency or farmers in order to prevent high uses of chemical for pest maintenance to reduce cost and environment pollution.